Performance evaluation of various cooling-lubrication techniques in grinding of hardened AISI 4340 steel with vitrified bonded CBN wheel - Damasceno, Ricardo Fernando [UNESP]; Ruzzi, Rodrigo de Souza [UNESP]; França, Thiago Valle [UNESP]; de Mello, Hamilton José [UNESP]; da Silva, Rosemar Batista; de Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2017)
In the grinding process, to achieve improved tribological conditions between wheel-chip-workpiece interfaces and minimize the effects of thermal damages, such as loss of hardness and cracks for example, it is needed to minimize the high amount of heat generated by the process. In addition to the correct adjusting of the cutting parameters, it is also to select an efficient coolant delivery technique (that includes coolant concentration, coolant flow rate, and nozzle geometry) and properties of abrasive wheels for successful grinding. Therefore, seeking for cooling-lubrication techniques with improved coolant efficiency and that can preserve surface integrity of the workpiece, as well as that make rational use of cutting fluids, becomes indispensable. Into this context, this investigation aims to evaluate the performance of different coolant-lubrication conditions during the surface grinding of AISI 4340 steel with a vitrified bonded CBN superabrasive wheel under various cutting conditions. Three coolant delivery techniques (flooding, MQL, and optimized Webster system) were tested. The input cutting parameters was depth of cut values (20, 50, and 80 μm). Tangential component force, specific energy, surface roughness, microhardness and surface residual stress of the machined surfaces, as well as abrasive wheel wear and G ratio were monitored and used to assess the performance of the different coolant-lubrication under the conditions investigated. The results showed that, in general, the optimized technique outperformed other coolant techniques in all the parameters evaluated because of the better access of cutting jet to the grinding area, especially at more severe cutting conditions. MQL technique exhibited superior performance in terms of cutting force and specific energy, but it was in general responsible for generation of poorer finishing and the highest microhardness variation in regions closer to machined surfaces. With regard the residual stresses, they were predominantly compressive, irrespective of the depth of cut and cooling-lubrication technique employed. A slight variation of the residual stresses values with depth of cut after machining with the optimized and the MQL coolant technique, unlike the pattern observed after machining with the conventional coolant delivery technique. Finally, no significant thermal damages or cracks were observed on the machined surfaces after machining under all the cutting conditions.
Keywords: AISI 4340 steel; CBN wheel; Cutting fluid; Grinding; Surface integrity